Using Output-Based Allocations to Manage Volatility and Leakage in Pollution Markets - Guy Meunier; Juan-Pablo Montero; Jean-Pierre Ponssard (Center for Economic Studies and ifo Institute (CESifo), 2017)
Output-based allocations (OBAs) are typically used in emission trading schemes to mitigate leakage in sectors at risk. Recent work has shown they may also help to stabilize prices in markets subject to supply and demand shocks. We extend previous work to simultaneously include both leakage and volatility. Motivated by discussions on how to reform carbon markets around the world, and in Europe in particular, we use our model to revisit several critical issues in the design of these markets. In particular, we look at how different OBA schemes manage permit price uctuations and what are the implications of deducting OBA permits (the majority going to trade-exposed and carbon intensive sectors) from the overall permit allocation, so as to keep the global cap on emissions fixed (as it is the case in California and in the EU).
Keywords: D24; L13; H23; L74; 330; pollution markets; carbon price volatility; output-based allocations